Ectomycorrhizal fungi and hyphosphere bacteria form a relay team to unlock chelated organic phosphorus for Pinus massoniana - Genyue Cao; Mengting Zhao; Xin Gao; Jie Zhang; Tingyu Zheng; Mengya Yu; Chuanchao Dai; Kai Sun; Yong Jia (Plant and Soil, 2026)

Pore-scale investigation of gravitational effects on underground hydrogen storage in aquifers using a high-stability lattice Boltzmann method - Tianyu Zuo; Jun Yao; Lei Zhang; Hai Sun; Yongfei Yang; Zhihao Xing; Wenxin Yang (Advances in Water Resources, 2026)

Competitive dissolution of binary minerals in porous media: A lattice Boltzmann study - Wenxin Yang; Hai Sun; Lei Zhang; Gloire Imani; Dongyan Fan; Junjie Zhong; Yongfei Yang; Jun Yao (Advances in Water Resources, 2025)

Pore scale modeling of wettability impact on CO2 capillary and dissolution trapping in natural porous media - Jinlei Wang; Yongfei Yang; Qi Zhang; Qi Wang; Huaisen Song; Hai Sun; Lei Zhang; Junjie Zhong; Kai Zhang; Jun Yao (Advances in Water Resources, 2025)

Effects of shrub microhabitats on taxonomic and functional diversity of soil microarthropods under grazing regimes in desertified regions - Jiancai Sun; Rentao Liu; Marcelo Sternberg; Zhimin Yang; Ying Tian (Applied Soil Ecology, 2025)

Genomic selection and its research progress in aquaculture breeding - Hailiang Song; Tian Dong; Xiaoyu Yan; Wei Wang; Zhaohui Tian; Ai Sun; Ying Dong; Hua Zhu; Hongxia Hu (Reviews in Aquaculture, 2023)
Since its introduction in 2001, genomic selection (GS) has progressed rapidly. As a research and application hot topic, GS has led to a revolution in the field of animal and plant breeding. Thanks to its ability to overcome the shortcomings of traditional breeding methods, GS has garnered increasing attention. Both theoretical and practical breeding studies have revealed the higher accuracy of GS than that of traditional breeding, which can accelerate genetic gain. In recent years, many GS studies have been conducted on aquaculture species, which have shown that GS produces higher prediction accuracy than traditional pedigree‐based method. The present study reviews the principles and processes, preconditions, advantages, analytical methods and factors influencing GS as well as the progress of research in aquaculture into these aspects. Furthermore, future directions of GS in aquaculture are also discussed, which should expand its application to more aquaculture species.